Modifikasi Rewinding Motor Induksi Satu Fasa Menjadi Tiga Fasa untuk Meningkatkan Efisiensi Daya Lisrik - I Gusti Bagus Alit Sudarma Putra; I Wayan Sutaya; Gede Indrawan (Jurnal Pendidikan Teknik Elektro Undiksha, 2025)
Induction motors are widely used as electric drives, although single-phase induction motors still have limitations in torque and efficiency. This study analyzes the performance of a single-phase induction motor and compares it with a rewound three-phase induction motor through laboratory testing. The research was conducted by applying various loading conditions and measuring rotational speed, force, current, input power, and output power. Torque was obtained from the measured force and moment arm, while efficiency was calculated based on the ratio of output power to input power. The results show that single-phase induction motor produced 1204.5W input power, 62.27% efficiency, and 5.796 Nm torque at 1410 rpm. In comparison, the three-phase induction motor generated torque up to 5.688 Nm at 1442 rpm, maximum output power of 780 W with 1070 W input power, and 70% efficiency. Overall, the three-phase induction motor demonstrates superior performance and better energy efficiency than the single-phase motor.